2018
DOI: 10.1111/1365-2435.13118
|View full text |Cite
|
Sign up to set email alerts
|

Responses of growing‐season soil respiration to water and nitrogen addition as affected by grazing intensity

Abstract: Most grasslands in the world, including the semi‐arid steppe in China, are threatened by nitrogen deposition, precipitation change and livestock grazing, which greatly affect soil carbon processes (e.g. soil respiration). Although the individual effects of nitrogen deposition and precipitation change on soil respiration are well understood, how their effects on soil respiration are altered by different grazing intensities is unclear. To determine how the effects of nitrogen deposition and precipitation change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…Other studies have also found that C inputs affected below‐ground primary consumers (microbial biomass) and secondary consumers (microbial‐feeding nematodes) but did not alter the third consumer trophic level (predatory nematodes; Scherber et al., 2010; Wardle et al., 2003). Consistent with previous studies (Chen et al., 2013; Li et al., 2018; Ren et al., 2018), we found that environmental resources (e.g. plant biomass, soil organic C and total soil N) decreased with increasing grazing intensity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other studies have also found that C inputs affected below‐ground primary consumers (microbial biomass) and secondary consumers (microbial‐feeding nematodes) but did not alter the third consumer trophic level (predatory nematodes; Scherber et al., 2010; Wardle et al., 2003). Consistent with previous studies (Chen et al., 2013; Li et al., 2018; Ren et al., 2018), we found that environmental resources (e.g. plant biomass, soil organic C and total soil N) decreased with increasing grazing intensity.…”
Section: Discussionsupporting
confidence: 92%
“…will depend on the historical grazing intensity); (b) Soil food webs will be most sensitive to the addition of N and W under moderate or heavy grazing intensity because the increases in resource availability will most benefit systems in which resource availability is most limited (Fanin et al, 2019); and (c) Lower trophic levels (micro-organisms) will be more sensitive to N and W addition than higher trophic levels (nematodes) because soil food webs are generally bottom-up controlled (Scherber et al, 2010;. The optimal range of grazing intensity in this region is about 1.5-2.0 sheep ha −1 year −1 , and the carrying capacity of grazing intensity is about 2.0-3.0 sheep ha −1 year −1 (Li et al, 2018;Shan et al, 2011). These values correspond to 4.5 to 6.0 and 6.0 to 9.0 sheep ha −1 season −1 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to an increase in livestock population, improper grazing management (e.g., overgrazing) gradually turns into a severe threat factor, affecting grassland ecosystem structure, function, and stability (Osem, Perevolotsky, & Kigel, 2002). Grazing has positive or negative effects on soil physicochemical properties (Steffens, Köelbl, Totsche, & Köegel-Knabner, 2008), soil nutrient cycling (He et al, 2011;Liu et al, 2018;Schuman, Reeder, Manley, Hart, & Manley, 1999), soil respiration (Li et al, 2018;Wang & Fang, 2009), and microbial community composition and structure (Randall et al, 2019), depending on grazing intensity (Han et al, 2008;Schönbach et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In line with an increasing precipitation trend in western parts of northern China and decreasing precipitation in eastern regions in recent decades [29,30], addition or reduction of water was applied in the season of concentrated precipitation and the plant growth season in the study area. The amount of water applied was determined using methods similar to those used in other related studies [31,32]. The water reduction device has a steel frame structure and a transparent V-shaped plastic plate to collect rainwater into a rain collection bucket.…”
Section: Experimental Designmentioning
confidence: 99%